SOURCES OF THE ELECTROPHYSIOLOGY AND ELECTROCARDIOGRAPHY - F. F. Tetenev; A. N. Stepanischeva (Бюллетень сибирской медицины)
The basic stages of development of electro-physiology and electrocardiography, 17 portraits and years of life of scientists, developing the fundamental aspects of electro-physiology, and also applied direction clinical electrocardiography, are presented in the article. By the most large scientists, developing fundamental    direction    in    electro-physiology    were    P. Arrhenius,    V.Yu. Chagovec,    Yu. Bernshteyn, A. Khodzhkin and E. Khaksli. In development of the applied direction in electrocardiography the role is great of V. Eyntkhoven, A.V. Samoilov and N. Holter. In period of formation of formation of electrophysiology, electrocardiography and at present scientists in ours country preferently working in applied direction.